NUEVAS ESPECIES CHILENAS DE XEROMELISSINAE (HYMENOPTERA: COLLETIDAE) - Toro, H.; Packer, L. (Acta Entomológica Chilena, 2022)
Two new species of Xeromelissinae are described, Chilimelissa rosie n.sp. from Toconao, II Región, Chile and Chilimelissa laureli n.sp from higher localities in the Andes Range, I Región, Chile.